Degree Square Subtraction Spectra and Energy - Macha, Jyoti Sachin; Shinde, Sumedha Narayan (Journal of the Indonesian Mathematical Society, 2022)
This paper defines and computes the degree square subtraction matrix, its characteristic polynomial and spectra in terms of the first Zagreb Index. We explore its bounds for spectral radius and energy.